2003
DOI: 10.1046/j.1365-2036.2003.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness in Canada of intravenous proton pump inhibitors for all patients presenting with acute upper gastrointestinal bleeding

Abstract: SUMMARYBackground: The administration of proton pump inhibitors intravenously after endoscopic treatment of peptic ulcers significantly reduces the recurrence of bleeding. Aim: To evaluate the incremental cost-effectiveness in Canada of intravenous proton pump inhibitor before endoscopic therapy to patients presenting with acute upper gastrointestinal bleeding, compared with endoscopic treatment alone. Methods: From a third-party payer perspective, we modelled the costs and effectiveness over 60 days of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 47 publications
5
29
0
2
Order By: Relevance
“…Recently, we have developed a statistical model using a hypothetical cohort of 1000 patients comparing a strategy of empirically treating all patients presenting to the emergency department with IV PPI infusion and endoscopic treatment versus endoscopic treatment alone (12). Based on the expected frequencies of endoscopically treatable ulcers and the efficacy of IV PPI from the study by Lau et al (6), significant cost savings can be realized with the use of IV PPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have developed a statistical model using a hypothetical cohort of 1000 patients comparing a strategy of empirically treating all patients presenting to the emergency department with IV PPI infusion and endoscopic treatment versus endoscopic treatment alone (12). Based on the expected frequencies of endoscopically treatable ulcers and the efficacy of IV PPI from the study by Lau et al (6), significant cost savings can be realized with the use of IV PPI.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, IV PPI was administered after endoscopic assessment with or without endoscopic therapy. Recently, cost analysis has suggested that IV PPI may be cost-effective if given before the endoscopic examination (12). Additionally, other Canadian National Registry studies have suggested that other patient groups may benefit from IV PPI.…”
mentioning
confidence: 99%
“…Of the three cost-effectiveness investigations evaluating the use of high-dose intravenous PPI therapy for acute peptic ulcer bleeding (11)(12)(13), only one was conducted from the perspective of a health care system in the United States (13). The latter study evaluated two scenarios involving second-look endoscopy (reendoscopy in all patients vs. re-endoscopy in patients at high risk for rebleeding), a scenario in which high-dose intravenous PPI therapy was given as an adjunct to therapeutic endoscopy and a usual care scenario in which patients only had a second endoscopy if signs of rebleeding occurred (no high-dose PPI) (13).…”
Section: Discussionmentioning
confidence: 99%
“…The three published cost-effectiveness studies that included at least one scenario involving PPI therapy used episodes of bleeding averted (11)(12), or in one case episodes of bleeding, surgery, or death averted (13), as the primary effectiveness outcome. In this investigation, effectiveness was primarily evaluated in terms of episodes of bleeding averted based on the studies underlying the clinical scenarios (14,15,17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation